Specifics of reporting on cash flows in insurance companies - Knežević, Snežana; Mitrović, Aleksandra; Sretić, Dušan (Hotel and Tourism Management, 2018)
The activity of insurance and operation of insurance companies is very important in the context of development of financial organizations that operate in the territory of many countries, including the Republic of Serbia. A report that is of crucial importance for insurance companies in the context of an adequate cash flow management is a cash flow statement. Bearing in mind the specificity of the insurance industry, as well as the risks associated with it, cash flow is the basic focus of financial management. For insurance companies, it presents an overview of cash flows that occurred during the previous accounting period. The aim of the paper is to show the importance of efficient cash flow management in insurance companies from the aspect of their planning, and to this effect, the paper provides the simulation of the internal report on cash flows that is done monthly for domestic insurance companies in the function of efficient liquidity management of the insurance company.